Characterization of a Dehydratase and Methyltransferase in the Biosynthesis of Ribosomally Synthesized and Post‐translationally Modified Peptides in Lachnospiraceae. (4th November 2019) - Huo, Liujie; Zhao, Xiling; Acedo, Jeella Z.; Estrada, Paola; Nair, Satish K.; van der Donk, Wilfred A.
Abstract: As a result of the exponential increase in genomic data, discovery of novel ribosomally synthesized and post‐translationally modified peptide natural products (RiPPs) has progressed rapidly in the past decade. The lanthipeptides are a major subset of RiPPs. Through genome mining we identified a novel lanthipeptide biosynthetic gene cluster ( lah ) from Lachnospiraceae bacterium C6A11, an anaerobic bacterium that is a member of the human microbiota and which is implicated in the development of host disease states such as type 2 diabetes and resistance to Clostridium difficile colonization. The lah cluster encodes at least seven putative precursor peptides and multiple post‐translational modification (PTM) enzymes. Two unusual class II lanthipeptide synthetases LahM1/M2 and a substrate‐tolerant S ‐adenosyl‐l ‐methionine (SAM)‐dependent methyltransferase LahSB are biochemically characterized in this study. We also present the crystal structure of LahSB in complex with product S ‐adenosylhomocysteine. This study sets the stage for further exploration of the final products of the lah pathway as well as their potential physiological functions in human/animal gut microbiota. Abstract : Go with your gut : Two unusual class II lanthipeptide synthetases and a SAM‐dependent C‐terminal methyltransferase are encoded in a novel lanthipeptide biosynthetic gene cluster ( lah ) from L. bacterium C6A11. These enzymes were biochemically characterized, setting the stage for further exploration of the final products and their physiological functions in gut microbiota.